Analisis Tingkat Kematangan Manajemen Proyek Pengembangan Perangkat Lunak Menggunakan Scrum Maturity Model: Studi Kasus PT. XYZ - Nuraminah, Ahlijati (LPPM of STIMIK ESQ, 2016)
Scrum is an agile framework designed for simplicity to produce software incrementally and iteratively involving collaboration between a team of developers and consumers. PT. XYZ has implemented Scrum since 2012, but there are problems in the implementation that projects dont achieve the time target of software development timeline. This research examines the maturity level of project management of software development that implement Scrum frameworks with quantitative research methodology using Scrum Maturity Model. Data were collected through questionnaires to the Scrum Master on software development projects that have implemented Scrum work. The conclusion from this research is PT. XYZ reached maturity level 2 Scrum Maturity Model. Recommendations for improvement are given to improve processes to achieve maturity level 3, 4, and 5.